Detecting spatial patterns of rivermouth processes using a geostatistical framework for near-real-time analysis. (November 2017) - Xu, Wenzhao; Collingsworth, Paris; Bailey, Barbara; Carlson Mazur, Martha; Schaeffer, Jeffrey; Minsker, Barbara
Abstract: This paper proposes a geospatial analysis framework and software to interpret water-quality sampling data from towed undulating vehicles in near-real time. The framework includes data quality assurance and quality control processes, automated kriging interpolation along undulating paths, and local hotspot and cluster analyses. These methods are implemented in an interactive Web application developed using the Shiny package in the R programming environment to support near-real time analysis along with 2- and 3-D visualizations. The approach is demonstrated using historical sampling data from an undulating vehicle deployed at three rivermouth sites in Lake Michigan during 2011. The normalized root-mean-square error (NRMSE) of the interpolation averages approximately 10% in 3-fold cross validation. The results show that the framework can be used to track river plume dynamics and provide insights on mixing, which could be related to wind and seiche events. Highlights: A geostatistical analyzing framework is developed for undulating sampling data. Hotspot and cluster analysis reveal river plume orientation and water mixing area. The framework supports near-real-time analysis and adaptive monitoring. The methods are implemented into an open source Web application in R.